Comparison of different conditions for accelerated ageing of small molecule organic solar cells - Hermenau, M; Leo, K; Riede, M (Society of Photo-Optical Instrumentation Engineers, 2010)
Besides efficiency and cost, lifetime is another important factor for the commercialisation of small molecule organic solar cells. To quickly achieve results one has to perform accelerated measurements. Thus, knowledge about accelerating factors is necessary to relate these results with measurements under real working conditions. Here, we compare different conditions for accelerated lifetime measurements of organic solar cells. The investigated p-i-n-devices contain a bulk heterojunction of Zinc-Phthalocyanine (ZnPc) and the fullerene C60 as photoactive materials. Doped layers of a large triarylamine-based amorphous wide gap material (Di-NPB) and C60 are used as hole and electron transport layer, respectively. For all devices, the IV characteristics are recorded during the entire measuring time. Unencapsulated solar cells show a rapid degradation due to the strong impact of atmospheric gases like oxygen or water vapour. Lifetimes (t80) of 43 to 110 hours are observed. Devices illuminated by blue light show a faster degradation than those exposed to red light. Additionally, the degradation is further accelerated when the intensity of blue light is increased. The comparison of external quantum efficiency measurements performed before and after ageing verifies that the used photoactive materials are stable. The intensity has the largest influence on degradation dynamics. Our results for solar cells illuminated by white light LEDs show that at intensities up to 100mW/cm2 the power conversion efficiency increases with time. This effect was observed over nearly 2000 hours of operation. An intensity of more than five suns is required to reduce the efficiency of our solar cells with time. This reduction is mainly driven by losses in the Fill Factor and a slight decrease of short circuit current density. Nevertheless, extrapolated lifetimes of up to 5000 hours are still observed. © 2010 SPIE.